THE IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION TO IMPROVE STUDENTS' LIFE-SKILLS IN AN ISLAMIC BOARDING SCHOOL - Fitriana Ulfa (Postgraduate Program, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to: (1) analyze the entrepreneurship education plan in fostering the life skills of students at the Walindo Manba'ul Falah Islamic Boarding School, Pekalongan Regency; (2) Analyzing the implementation of entrepreneurship education in fostering the life skills of students at the Walindo Manba'ul Falah Islamic Boarding School, Pekalongan Regency; and (3) to analyze the evaluation of entrepreneurship education in fostering the life skills of students at the Walindo Manba'ul Falah Islamic Boarding School, Pekalongan Regency. By using a qualitative approach, data collection was done through observation, interviews, and documentation. In-depth interviews were conducted with several related parties, namely boarding school caregivers, Islamic boarding school leaders, coordinators of pesantren business units, and business unit managers. Data analysis techniques by reducing data, displaying data, and drawing conclusions. Examination of the validity of the data by means of triangulation of sources and techniques and combined with theory. The results of the study show that: first, planning for entrepreneurship education at the Walindo Manba'ul Falah Islamic boarding school in Pekalongan Regency is carried out in two forms, namely practice-based planning and planning through hidden curriculum. Second, in practice, entrepreneurship education at the Walindo Manba'ul Falah Islamic boarding school, Pekalongan Regency applies a